2019
DOI: 10.1016/j.cjtee.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Buttress plate fixation of coronoid process fractures via a medial approach

Abstract: PurposeTo assess the clinical and radiographic outcomes of coronoid process fractures surgically managed with buttress plate fixation via a medial approach.MethodsA retrospective review of all coronoid fractures surgically fixed in our institution using a buttress plate technique via a medial approach between June 2012 and April 2015 by the senior author was performed. These fractures were all sizeable fractures contributing to persistent elbow instability in terrible triad or varus posteromedial rotatory inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In a study by Muñoz et al, 18 the complication rate was 27%, with only 6 patients (9.7%) being subjected to reoperations, where 2 of them were reoperated because of postsurgical stiffness. In another study, Lor et al 10 reported only 1 case of infection and 1 case of heterotopic ossification.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a study by Muñoz et al, 18 the complication rate was 27%, with only 6 patients (9.7%) being subjected to reoperations, where 2 of them were reoperated because of postsurgical stiffness. In another study, Lor et al 10 reported only 1 case of infection and 1 case of heterotopic ossification.…”
Section: Discussionmentioning
confidence: 93%
“…In another study reporting 8 patients with PMRV, all anteromedial coronoid fractures were fixed using a 1.5- or 2.0-mm “T” buttress plate. 10 They report an average flexion-extension arc of 130° and a MEPS evaluation of 75 points without reoperations or persistent instability at a short-term follow-up. These previous studies and ours shows the importance of performing an anatomic reduction and stable fixation of the anteromedial facet of the coronoid, allowing to recover the stabilizer role against posterior translation and posteromedial rotation.…”
Section: Discussionmentioning
confidence: 95%
“…Several surgical methods, such as suture lasso, 13 14) lasso plate, 15) screw fixation, 16) tension band wiring, 17) and buttress plate fixation, 18) have been introduced for coronoid fractures. Suture lassos have been widely used as an effective fixation method for smaller fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this fracture often results in early arthritis and elbow instability, most studies recommend internal fixation for AMFs. Surgical interventions of AMFs are controversial ( 24 , 35 , 36 ). Park ( 24 ) described the standard treatment for AMFs based on the acceptable clinical outcomes and elbow ROM after the management of 11 AMF fractures: LCL repairing alone for O'Driscoll type 2-1, fragments fixation with repairing LCL for O'Driscoll type 2-2, 2–3.…”
Section: Treatment Strategies Based On Classificationmentioning
confidence: 99%
“…Whether to perform fracture fixation alone, ligament repair alone, or a combination of both depends on the size of the fracture and the extent of soft tissue damage. Buttress plate fixation via a medial approach was also a reliable method of treatment that produces satisfactory and predictable outcomes (36). However, some studies believe that even small fragments should be treated.…”
Section: Amf Fracturesmentioning
confidence: 99%